El efecto de practicas agronomicas sobre el nivel poblacional de afidos y virosis en Carica papaya L. - Robles, W.=700 1 Pantoja, A.; Abrew, E.; Peña, J.; Ortiz, J.; Lugo, M. de L.; Cortes, M.; Macchiavelli, R.
(Es, En)
Ilus., 27 ref.
Keywords: CARICA PAPAYA; CONTROL DE PLAGAS; APHIDOIDEA; VIROSIS; DINAMICA DE POBLACIONES; MANEJO DEL CULTIVO; COSTA RICA